National debt and corruption: evidence from SADC - Mashaba, Kgodisho Mampye (My University, 2022)
The national debt burden is an economic issue which gained attention from scholars, economists, and the society. Increased national debt emerged after the financial crisis nationally and internationally. There are many academic studies that investigate the nexus between national debt and Gross Domestic Product. However, it is rare to find academic research investigating the role played by corruption on debt. Due to this gap in the literature, the thesis examines the impact of corruption on national debt in the SADC region from the year 1995 to 2020. The Johansen test results for cointegration shows that there is cointegration among the variables employed in this thesis. The results for ARDL Bound test confirms cointegration, meaning that there is a long-run nexus between the variables. The ECM is used to measure the speed of adjustment to check how quickly the variables converge back to equilibrium in the long run. The results shows that the market will correct itself in the long run. Other tests, such as stability diagnostic check, were conducted indicating that the residuals are normally distributed. SADC countries are known to be rich in minerals, but they lack capital, therefore, this thesis recommends that, SADC countries should continue borrowing from financial institutions to finance capital accumulation. However, anti-corruption programmes must be strengthened to ensure that borrowing does not lead to subdued economic growth.
A research report submitted in partial fulfilment of the Degree of Master of Commerce in Applied Development Economics to the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2022